1995
DOI: 10.1007/bf01818893
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and autonomic function in traumatic lower limb amputees

Abstract: This study examined plasma insulin response to oral glucose load and autonomic nervous system activity in male lower limb amputees (n = 52) aged 50-65 years, compared to matched controls (n = 53). The groups had similar body mass index, blood pressure and plasma lipid levels. The amputees had higher mean fasting plasma insulin levels (18.4 +/- 9.7 (SD) versus 13.7 +/- 5.1 mU/l, p = 0.005) and during an oral glucose tolerance test (OGTT) (1 h levels 88.1 +/- 45.3 versus 62.1 +/- 42.7, p = 0.016) with similar pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
1
27
0
2
Order By: Relevance
“…Furthermore, the release and the sensitivity of norepinephrine are increased in this condition [29]. Although the present study did not evaluate sympathetic nerve activity in traumatic lower limb amputees, Peles et al [30] observed an increase in plasma norepinephrine levels in this population. The authors raised the hypothesis that compression caused by the prosthesis and physical overload promotes an increase in sympathetic nerve activity and shear forces, causing endothelial dysfunction and increasing blood pressure levels.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, the release and the sensitivity of norepinephrine are increased in this condition [29]. Although the present study did not evaluate sympathetic nerve activity in traumatic lower limb amputees, Peles et al [30] observed an increase in plasma norepinephrine levels in this population. The authors raised the hypothesis that compression caused by the prosthesis and physical overload promotes an increase in sympathetic nerve activity and shear forces, causing endothelial dysfunction and increasing blood pressure levels.…”
Section: Discussionmentioning
confidence: 82%
“…97 When compared to uninjured controls with no difference in body mass index, blood pressure, or lipid levels, persons with LL exhibited significantly higher increased fasting plasma insulin levels as well as insulin resistance. 96 Increased plasma insulin levels and insulin resistance are risk factors for atherosclerosis and metabolic syndrome, considered precursors to CVD. The role of psychological stressors in the development of CVD is not well understood; however, psychosocial factors have demonstrated involvement in the pathogenesis of CVD.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Peles et al compared the insulin resistance between lower limb amputees and healthy controls with similar age, body mass index, blood pressure and plasma lipid levels. Amputees were found to have significantly higher fasting plasma insulin levels and insulin response to oral glucose with similar plasma glucose levels [27]. Modan et al also showed increased levels of insulin in amputees compared to healthy controls after adjustment for age, smoking, physical activity, body mass index, mean arterial blood pressure and cholesterol [28].…”
Section: Discussionmentioning
confidence: 99%